Assessing the Impact of Precancerous Lesions on Oral Health-Related Quality of Life: A Study at Tertiary Care Hospital - Shilpa A Warhekar; Gaurao M Pimpale; Ashish M Warhekar; Ranu S Ingole; Yogesh S Ingole (Wolters Kluwer Medknow Publications, 2024)
Objective: The aim of this cross-sectional study was to assess the oral health-related quality of life (OHRQoL) in a cohort of 500 patients diagnosed with precancerous lesions and conditions at a tertiary care hospital in Central India. Methods: 500 patients with confirmed precancerous oral lesions and conditions were recruited for the study. The Oral Health Impact Profile (OHIP-14) questionnaire, a validated instrument consisting of 14 items, was used to assess the OHRQoL of the participants. The OHIP-14 questionnaire scores were statistically analyzed using appropriate methods. Results: The majority of the participants were with a mean age of 48 years. The mean OHIP-14 score was calculated to be 45.1, indicating the overall impact of oral health on the quality of life of patients with precancerous lesions and conditions. The individual domains most affected were functional limitations and physical pain. Conclusion: This study demonstrates that promoting oral health awareness and regular screenings in the community is needed to prevent the progression of oral precancerous conditions and ultimately reduce the burden of oral cancer.